Pengaruh implementasi AI dan Scratch melalui PjBL Terhadap Kemampuan Computational Thinking Siswa Sekolah Dasar - Setiawan, Arif; Irawan, Yosan Ananda (Jurnal Riset dan Inovasi Pembelajaran, 2025)
In today's digital age, computational thinking (CT) skills are essential, especially in education. Challenges arise in teaching CT to elementary school students, who often have difficulty in understanding computer logic and computer-based problem-solving approaches. This study aims to evaluate the effectiveness of using Artificial Intelligence (AI) and Scratch-based learning in improving 6th grade students' CT skills at Al Abidin ICT Elementary School. The research method used was quasi-experimental with experimental and control groups, where the experimental group received AI and Scratch learning interventions. Data were collected through pretest and posttest, and analyzed using SPSS. The results showed a significant improvement in CT skills in the experimental group, with statistical analysis results supporting the significant effect of AI learning. Students' responses to the learning platform www.aikids.id were also mostly positive. These results confirm that AI learning can be an effective approach to developing CT at the primary school level, with an impact not only on CT ability but also students' motivation and engagement in learning.